2022
DOI: 10.1039/d1cp05723e
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Brønsted–Evans–Polanyi relationship for the hydrogen evolution reaction on transition metals based on constant electrode potential density functional theory

Abstract: In the search for efficient and inexpensive electrocatalysts for the hydrogen evolution reaction (HER), the hydrogen binding energy (ΔG*H) is often used as a descriptor to represent the catalytic activity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…52 The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. 53,54 This approach has been used by our group 5,53−58 and others 59−66 to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions.…”
Section: Pbe-d3mentioning
confidence: 99%
See 1 more Smart Citation
“…52 The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. 53,54 This approach has been used by our group 5,53−58 and others 59−66 to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions.…”
Section: Pbe-d3mentioning
confidence: 99%
“…The linear Poisson–Boltzmann implicit solvation model as implemented in VASPsol with a Debye screening length of 3.0 Å was utilized to simulate water (dielectric constant = 78.4) and the electrolyte and maintain the neutrality of the simulation cell . The details regarding how to correct the electronic energy due to an electron being added to or removed from the system and how to construct free energy surfaces can be found in the Supporting Information (SI) or our previous works. , This approach has been used by our group , and others to study a variety of electrochemical reactions. Some recent theoretical studies have suggested that better thermodynamics of overall electrochemical reactions can be achieved by correcting the computed free energies of the gas molecules involved in the reactions. We found that applying the correction suggested by Calle-Vallejo and co-workers to CO 2 , which is the only molecule in the current system, leads to no change in our major conclusions (Table S2).…”
Section: Computational Detailsmentioning
confidence: 99%
“…For periodic systems, transition states are commonly computed using the climbing image nudged elastic band calculations. , Another effective way to obtain the kinetic barrier is the Brønsted–Evans–Polanyi (BEP) relationship. , It relates the kinetic barrier to the corresponding reaction energy for a class of materials: Δ G ‡ = βΔ G + α, where Δ G ‡ , β, Δ G , and α are the kinetic barrier, BEP coefficient, reaction energy, and a constant, respectively. The BEP relationship allows one to estimate the kinetic barrier by simply calculating the reaction energy, leading to a significant reduction in computational costs and permitting high-throughput screening of materials. , For EC, its main approximation is that the transition state for the nonelectrochemical step is equivalent to that of the electrochemical step at a specific potential U …”
Section: Methodsmentioning
confidence: 99%
“…The BEP relationship allows one to estimate the kinetic barrier by simply calculating the reaction energy, leading to a significant reduction in computational costs and permitting highthroughput screening of materials. 210,211 For EC, its main approximation is that the transition state for the nonelectrochemical step is equivalent to that of the electrochemical step at a specific potential U. 203 Microkinetic modeling is not computationally demanding; however, it deals with averages, and hence it lacks the capabilities to probe the catalyst surface on the atomistic level, such as tracing the effects of adsorbate relative positions, i.e., lateral interactions and cooperative effects.…”
Section: Microkinetic Modelingmentioning
confidence: 99%
“…A Debye length of 3.0 Å was utilized in the solvation model. This constant electrode potential model has been employed by our research group as well as other researchers to investigate a wide range of electrochemical reactions. The details regarding the correction of the electronic energy resulting from altering the number of electrons in the system as well as the correction from the electronic energy to the free energy surfaces can be found in the Supporting Information.…”
Section: Computational and Experimental Detailsmentioning
confidence: 99%